Pengasuhan Oleh Ibu Menurunkan Resiko Gangguan Perkembangan Bahasa Pada Anak Usia 1 Tahun - Erni Dwi Widyana; Tarsikah Tarsikah (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2019)
The first years of life are a golden period for brain growth and development of children, especially language. Speech and language disorders are one of the most common causes of developmental disorders in children. The aim of this study was to determine the factors that most influence language development in children aged 1 year. The design used analytic survey with cross sectional approach, with a population of 80 respondents aged 1 year, with a sample of 67 respondents who met the inclusion criteria. The research instrument used a questionnaire and a Denver II sheet. Data were analyzed by logistic regression test with the results of the gender variable obtained ? value 0.013 and the care variable obtained ? value 0.044, then gender and parenting affect the language development in children aged 1 year. In an effort to reduce the prevalence of language delays in children aged 1 year, midwives should conduct early detection or monitoring language development that can be done by using Denver II to optimize children's language development. Keywords: Language Development, Parenting, One Year Old Children